Soggettività tributaria e tassabilità delle attività d’impresa nei luoghi religiosi (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Attività d’impresa degli enti religiosi: il contenzioso come indicatore di performance del sistema italiano delle esenzioni - 2. L’endiadi ente/attività nella giurisprudenza: un caso recente - 3. I centri culturali islamici e i Gurdwara sikh: dalla indefinibilità alle soggettività del terzo settore - 4. Segue: La particolare difficoltà di qualificazione delle attività d’impresa nei luoghi di culto islamici - 5. Attività e accesso alle agevolazioni tributarie: la non discriminazione attraverso il Codice del Terzo settore (CTS) - 6. Segue: Le APS islamiche: la positiva esperienza nel Comune di Torino rispetto alla riconoscibilità dei soggettivi passivi tributari - 7. L’autonomia imperfetta, o secondo diritto comune, degli enti delle religioni prive di intesa.Tax subjectivity and taxability of business activities held in religious placesABSTRACT: The activities of ecclesiastical institutions, different from those of worship and religion and carried out by entrepreneurial method and rules of the free market, are subject to ordinary taxation. Otherwise, according to our Supreme Court and the European Court of Justice, they would go against the ban of so called incompatible state aid (art. 107, § 1, TFEU), as the status that every national law acknowledges to a artificial person is irrelevant. The Islamic cultural centers, the Sikh Gurdwara are generally in a limbo with a possible discrimination in the enforcement of the regulation under art. 8 of the Constitution. This paper, however, points out a few associative models, that the ecclesiastical institutions could implement so that their religious places can enjoy at least the common exemptions.